The immunopathogenesis of SARS‐CoV‐2 infection in children: diagnostics, treatment and prevention - Harsita Patel; Andrew McArdle; Eleanor Seaby; Michael Levin; Elizabeth Whittaker (Clinical & Translational Immunology, 2022)
Abstract Symptoms and outcomes for paediatric COVID‐19 differ vastly from those for adults, with much lower morbidity and mortality. Immunopathogenesis drives severe outcomes in adults, and it is likely that age‐related differences in both the innate and specific immune responses underlie much of the variation. Understanding the protective features of the paediatric immune system may be crucial to better elucidate disease severity in adult COVID‐19 and may pave the way for novel therapeutic approaches. However, as well as uncommon cases of severe paediatric acute COVID‐19, there have been children who have presented with delayed multisystem inflammation, including cardiac, gastrointestinal, skin, mucosa and central nervous system involvement. The occurrence of coronary artery aneurysms has drawn comparisons with Kawasaki Disease, but similarities with the inflammatory phase of adult acute COVID‐19 have also been drawn. In this review, we summarise findings from studies investigating pre‐existing immunity, cytokine profiles, innate, B‐cell, antibody, T‐cell and vaccine responses in children with acute COVID‐19 and multisystem inflammation, compared with COVID‐19 adults and controls. We further consider the relevance to therapeutics in the context of limited evidence in children and highlight key questions to be answered about the immune response of children to SARS‐CoV‐2.